Honest to God and the South African churches in 2016 - M. Prozesky (Acta Theologica)
The year 2013 was fifty years since the publication of Honest to God, by John A.T. Robinson (1919-1983), who was Bishop of Woolwich at the time. The book became a bestseller. The research question that gave rise to the present article is how relevant and sound its main ideas are for South Africa, in particular, and for his own church in 2016. This paper examines Robinson’s views from three  perspectives, namely Christian and secular practical ethics, the recent history of the church, to which the Bishop belonged in England, and the contemporary South African situation, in particular. The paper argues that, five hundred years on, Robinson’s project of developing a Christian response to contemporary secular challenges remains valid in South Africa.